The Use of Glucocorticoids in Lupus Nephritis: New Pathways for an Old Drug - Mejía-Vilet, Juan M.; Ayoub, Isabelle (Frontiers in Medicine, 2021)
Glucocorticoids therapy has greatly improved the outcome of lupus nephritis patients. Since their discovery, their adverse effects have counterbalanced their beneficial anti-inflammatory effects. Glucocorticoids exert their effects through both genomic and non-genomic pathways. Differential activation of these pathways is clinically relevant in terms of benefit and adverse effects. Ongoing aims in lupus nephritis treatment development focus on a better use of glucocorticoids combined with immunosuppressant drugs and biologics. Newer regimens aim to decrease the peak glucocorticoid dose, allow a rapid glucocorticoid tapering, and intend to control disease activity with a lower cumulative glucocorticoid exposure. In this review we discuss the mechanisms, adverse effects and recent strategies to limit glucocorticoid exposure without compromising treatment efficacy.